A STEGENOGRAPHY IN 3D MESH BY REARRANGING THE ORDER OF VERTEX PRESENTATION - Thái Duy Quý (Tạp chí Khoa học Đại học Đà Lạt)
This paper proposes a method of data hiding approach on 3D mesh objects in the representation domain by rearranging the order of the vertices based on a secret key string (a list vertex that was previously traversed as highly secret). This method can be applied to the vertex order, the order of polygon and the order index of polygon. This method also ensures the safety of data; each application can embed a little bit per vertex that not changes to the cover objects.